2020
DOI: 10.5296/ije.v12i3.17136
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Attitudes and Achievement in Mathematics among Ghanaian JHS Students

Abstract: Students’ learning and performance in mathematics is affected by several factors, including students’ attitude. This paper aims to understand the gender differences in attitude toward mathematics and mathematics achievement. A descriptive survey design was used, and the participants consisted of 360 Junior High School students. Two instruments, semi-structured questionnaire and students test scores were used. The results revealed that, in general, both female and male students held positive attitudes towards m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 13 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…These findings suggest that girls' attitudes towards mathematics are significantly influenced by their perceptions of their teachers' behaviour, highlighting the importance of positive teacher-student interactions in shaping students' attitudes towards the subject. The findings reveal a significant positive correlation between students' perception of their teachers' behavior and three attitudinal variables: anxiety, perception of mathematics as a male domain, and self-confidence, suggesting that a positive teacher-student relationship promotes favourable student attitudes [1,4,15,20,24]. This finding aligns with research by Mata et al, [16] who highlighted the influential role of teacher-student relationships on overall school and behavioural adjustment.…”
Section: Correlation Between Girls' Perceptions Of Teachers' Behaviou...supporting
confidence: 80%
See 4 more Smart Citations
“…These findings suggest that girls' attitudes towards mathematics are significantly influenced by their perceptions of their teachers' behaviour, highlighting the importance of positive teacher-student interactions in shaping students' attitudes towards the subject. The findings reveal a significant positive correlation between students' perception of their teachers' behavior and three attitudinal variables: anxiety, perception of mathematics as a male domain, and self-confidence, suggesting that a positive teacher-student relationship promotes favourable student attitudes [1,4,15,20,24]. This finding aligns with research by Mata et al, [16] who highlighted the influential role of teacher-student relationships on overall school and behavioural adjustment.…”
Section: Correlation Between Girls' Perceptions Of Teachers' Behaviou...supporting
confidence: 80%
“…This finding aligns with research by Mata et al, [16] who highlighted the influential role of teacher-student relationships on overall school and behavioural adjustment. Similarly, Poku & Ampadu, [20] found that positive teacher-student relationships, characterized by warmth and communication, correlate with behavioural competency and better school adjustment. Additionally, Madu et al, [15] findings underscore the negative impact of teachers' negative attitudes on students' attitudes toward mathematics.…”
Section: Correlation Between Girls' Perceptions Of Teachers' Behaviou...mentioning
confidence: 87%
See 3 more Smart Citations